BUILDING INFORMATION MODELING BASED COMPARISON STUDY ON ENERGY INFRASTRUCTURE PROJECT USING INDUSTRIALIZED BUILDING SYSTEM AND CONVENTIONAL METHOD - Usman, Fathoni; Hamim, Sumi Amariena (Jurusan Teknik Sipil & Perencanaan Fakultas Teknik Universitas Sriwijaya, 2018)
Construction industry in Malaysia has moved forward into technology-driven where its transition is in progress from conventional method to a more advanced and mechanized system known as the Industrialized Building System (IBS). This paper presents economic aspects of using Interlocking Hollow Brick System (IHBS) in the construction of the Primary Distribution Sub-station (PPU) of energy infrastructure asset development. The main objective is to compare the difference in construction method between IHBS with the conventional method. The study is focused on comparing various aspects of using interlocking block system in terms of time, costs, and utilization of workforce. Building Information Modelling tools in this study are used. From the analysis and modeling of the PPU, it is shown that the implementation of IHBS can reduce construction time, cost, and utilization of workforce up to 40% - 50% as compared to the conventional method. The construction time using IHBS can be reduced up to 48% as compared to the conventional construction method.